Adapting Strategically to Changing Times in Health Professions Education: A Generational Workshop for Educators - Stefanie M. Attardi; Tracey A.H. Taylor; Sarah Lerchenfeldt; Rebecca L. Pratt; Kara E. Sawarynski (Association of American Medical Colleges, 2021)
Introduction Health professions classrooms are filled with a new generation of students: iGen/generation Z. Much is known about millennials' educational needs, but they no longer comprise the majority of student populations. Research indicates that curricular strategies once useful for millennials may be ineffective for iGen. Due to multiple and surprising generational differences including ubiquitous technology, verbal/social/reading skills, and attention spans, educators might struggle to reach iGen members and are encouraged to re-examine instructional methods with iGen in mind. Methods We designed this 90-minute workshop to give educators an informed understanding of iGen and discuss curricular adaptations intended to maintain educational quality through a literature-based presentation, self-assessment activities, and case discussions. We delivered the session to multiple diverse groups of health professions educators and staff. The attendees evaluated the workshop's quality and its longitudinal impact using 5-point Likert-style agreement surveys. Results Respondents deemed the topic crucial to professional development and rated the content highly relevant (100% agreement/strong agreement). Longitudinal respondents could recognize iGen and personal characteristics (79% agreement or strong agreement) and the majority (58%) agreed/strongly agreed they were able to implement new instructional strategies. Discussion Although educators are aware of typical generational differences, many are surprised to learn the unique attributes of their iGen student population. Workshop participation allowed educators to better understand both iGen students as well as how their own generational characteristics might relate to iGen members. Gaining this perspective allows educators to more adeptly create and deliver content to current health professions students.